The Poetry of Brecht : Seven Studies - Thomson, Philip (Chapel Hill The University of North Carolina Press, 1989)
Though not a survey of Bertolt Brecht's poetry, this book covers the major periods in his work and most of its major themes as well. Each of the seven chapters deals with a segment from Brecht's considerably poetic opus. A central characteristic of Brecht's poetry is its dual function, as self-revelation and self-concealment. This emerges most clearly in the poet's relationship to his reader for whom Brecht dons a variety of guises, plays a variety of roles, and speaks in a variety of voices. Thomson's methodology is pluralist, although he includes a discussion of how reader-response theory can be harnessed to the task of interpreting Brecht's poetry. Various means of interpretation and analysis are used, depending on which seems to yield the most information and insight. The only reading of Brecht's poetry categorically refused is the one that accepts it at face value as a record of Brecht's life experience. Despite outward appearances, Brecht is a devious writer, and nowhere more so than in his poetry, where he most immediately presents himself to his public.
National Endowment for the Humanities
Andrew W. Mellon Foundation
English
Keywords: Literature: history & criticism; Poetry; German Studies; Literature